Pengaruh Model Inkuiri Terbimbing Berbantuan Geogebra Terhadap Kemampuan Pemecahan Masalah Matematika Peserta Didik - Irmawati; Hakim, Fauziah; Anaguna, Nursyam (Journal of Health, Education, Economics, Science, and Technology, 2025)
The aim of this research is to find out whether the guided inquiry learning model assisted by Geogebra media has a positive effect on the mathematical problem solving abilities of class VIII students at SMPN Katumbangan Lemo. This type of research is a quasi-experiment in the form of a nonequivalent control group design. This research was carried out at SMPN Katumbangan Lemo in the 2023/2024 academic year, where class VIIIC was used as the experimental class and class VIIID as the control class. Data collection techniques were carried out by giving tests of mathematical problem solving abilities and observation sheets. The data analysis technique uses descriptive analysis and inferential analysis with the help of the SPSS 23 program. Descriptive statistical analysis results in an average posttest score for the experimental class of 78.11, while for the control class the average posttest score is 70.68. The results of the hypothesis using the Independent Sample T-Test, a significance value of 0.000 < 0,05 was obtained so it was accepted, meaning that the guided inquiry learning model assisted by Geogebra media had a positive effect on the mathematical problem-solving abilities of class VIII students at SMPN Katumbangan Lemo.